Expression of CD1d by astrocytes corresponds with relative activity in multiple sclerosis lesions - Muir, Fraser G.W. (Brain Pathol, 2019)
The CD1 protein family present lipid antigens to the immune system. CD1d has been observed in the CNS of MS patients, yet no studies have quantitatively characterized this expression and related it to inflammatory demyelinative activity in MS plaques. In this study, we set out to localize and quantify the presence of CD1d expression by astrocytes in MS brain tissue lesions. Formalin‐fixed, paraffin‐embedded MS and control brain tissues were examined. Lesions were classified as active, chronic active or chronic silent. Using immunofluorescence, the density of CD1d‐positive cells was determined in active lesions, chronic active lesion edges and chronic active lesion centers. The percentage of CD1d‐positive cells that were GFAP‐positive was also determined in each of these regions. CD1d immunoreactivity was significantly increased in MS compared to control tissue, was significantly more prevalent in areas of active demyelination, and colocalized with GFAP‐positive reactive astrocytes. Increases of CD1d immunoreactivity in the CNS of MS patients being greatest in areas of active demyelination and localized to GFAP‐positive astrocytes lend support to the hypothesis of a lipid‐targeted autoimmune process contributing to the pathogenesis of MS.